128k views
0 votes
Subtract (5x^2+3)-(2x^2+4x-12)

User Ella Ryan
by
6.7k points

2 Answers

5 votes

Answer:

(5x² + 3) - ( 2x² + 4x - 12) = 3x² - 4x + 15

Explanation:

The given expression is

(5x² + 3) - ( 2x² + 4x - 12)

To find the subtraction result

(5x² + 3) - ( 2x² + 4x - 12) = 5x² + 3 - 2x² - 4x + 12

= 5x² - 2x² - 4x + 3 + 12

= 3x² - 4x + 15

Therefore the correct answer is

(5x² + 3) - ( 2x² + 4x - 12) = 3x² - 4x + 15

User Matt Goodall
by
5.8k points
1 vote

Answer:

Final answer is
3x^2-4x+15

Explanation:

Given expression is
(5x^2+3)-(2x^2+4x-12).

Now we need to subtract them.

We are allowed to subtract like terms only that has same variable with same exponent.


(5x^2+3)-(2x^2+4x-12)


=5x^2+3-2x^2-4x+12


=5x^2-2x^2-4x+3+12


=(5-2)x^2-4x+(3+12)


=(3)x^2-4x+(15)


=3x^2-4x+15

Hence final answer is
3x^2-4x+15

User Aaron Thomas
by
5.9k points